The Asteraceae family in Los Mármoles National Park, Hidalgo, México - García-Sánchez, Carlos Alberto; Sánchez-González, Arturo; Villaseñor, José Luis (Instituto de Ecología, A.C., 2014)
An inventory of the species of Asteraceae occurring in the Los Mármoles National Park (PNM) was carried out; this park is located in the northwestern part of the state of Hidalgo. In the PNM, six different vegetation types are found, the Pinus-Quercus and Quercus forests being the dominating ones. A total of 101 species of Asteraceae was recorded, distributed in 13 tribes and 51 genera; two species are alien (exotics) for the flora of Mexico. Members of the tribes Eupatorieae (26 species), Heliantheae (17), Astereae (11), and Coreopsideae (10) predominated. The genera with the highest number of species are Ageratina (11), Stevia (11), Pseudognaphalium (6), and Dahlia (5). Species endemic to Mexico constitute the main component (54), followed by those distributed from Mexico to Central America (16); only five species (including the two exotics) also occur in the Old World. The use of non-parametric estimators indicated that the degree of completeness of the Asteraceae flora known to date for the park ranges between 70 and 84%.